Mitigating heat stress by reducing solar exposure in pedestrian routing - Kolaxidis, Nikolaos; Ludwig, Christina; Knoblauch, Steffen; Fürle, Johannes; Foshag, Kathrin; Fendrich, Sascha; Lautenbach, Sven; Zipf, Alexander (Transactions in GIS, 2025)
Due to climate change, heat stress is an increasing health risk in cities that requires adaptation measures from both citizens and city planning. This study proposes a routing service to reduce solar exposure for pedestrians and investigates its potential to reduce heat stress from both individual and planning perspectives. As a case study, the solar exposure of the pedestrian paths in the city of Heidelberg, Germany, was modeled throughout the day and subsequently integrated into a specialized routing service. Consideration of shade in route suggestions allowed a relevant reduction of solar exposure with minimal detours. In most cases, solar exposure was reduced by 12 to 26%, with occasional reductions of up to 90%. These findings highlight the added value of considering alternative route options to avoid solar exposure. As city dwellers can spatially and temporally adjust their paths using this routing service, they may simply bypass some hot spots, which is especially true for highly urbanized areas. However, reasonable alternatives to reduce solar exposure were not available everywhere. Therefore, action from city planners is still necessary. A network analysis identified critical roads in the city where adaptation measures, such as additional shade from trees or man-made structures, could have the greatest impact on reducing pedestrian heat stress. It also showed that the spatial configuration of the city, including anthropogenic and natural factors, plays a crucial role in the planning of adaptation to urban heat. While the approach is generally transferable to regions with similar topological and environmental characteristics, it should be evaluated with respect to local conditions before being applied in different contexts.